Actual and preferred working hours - René Böheim; Mark P. Taylor (University of Essex, Institute for Social and Economic Research (ISER), 2001)
In this paper, we use data from the British Household Panel Survey to test the traditional labour supply model by investigating whether subjective data on desired labour supply provide information on future adjustment of actual hours worked. Our estimates suggest that male and female employees, particularly job changers and men working part-time, are able to adjust their work hours in line with preferences. Our evidence indicates that working hours are not driven by labour demand alone.
Keywords: 330